2008
DOI: 10.1063/1.2857463
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of amorphous InGaZnO4 thin film transistors and their subgap density of states

Abstract: We report a model of the carrier transport and the subgap density of states in amorphous InGaZnO 4 ͑a-IGZO͒ for device simulation of a-IGZO thin-film transistors ͑TFTs͒ operated in both the depletion mode and the enhancement mode. A simple model using a constant mobility and two-step subgap density of states reproduced well the characteristics of the a-IGZO TFTs. a-IGZO exhibits low densities of tail states and deep gap states, leading to small subthreshold swings and high mobilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
207
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 333 publications
(224 citation statements)
references
References 16 publications
17
207
0
Order By: Relevance
“…11) On the other hand, Hall mobilities (® Hall ) and field-effect mobilities (® FE ) of a-IGZO TFTs with the chemical composition of In:Ga:Zn³1:1:1 in atomic ratio are reported to be 1015 cm 2 /Vs, 1),12) but some reports have provided much larger mobilities. Based on the device physics, ® FE should be smaller than drift mobility (³® Hall ) because ® FE include the deterioration effects by electron traps in the band gap and carrier scattering at the channelgate insulator interface; 13) actually, we have confirmed that ® FE of our a-IGZO TFTs are close to or a little bit smaller than ® Hall . 1), 13) In this work, we investigated the effects of an O 2 -and ozone-(O 3 -) annealing combined process on characteristics of a-IGZO TFTs, and observed a high saturation mobility (® sat ) of ³30 cm 2 / Vs.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…11) On the other hand, Hall mobilities (® Hall ) and field-effect mobilities (® FE ) of a-IGZO TFTs with the chemical composition of In:Ga:Zn³1:1:1 in atomic ratio are reported to be 1015 cm 2 /Vs, 1),12) but some reports have provided much larger mobilities. Based on the device physics, ® FE should be smaller than drift mobility (³® Hall ) because ® FE include the deterioration effects by electron traps in the band gap and carrier scattering at the channelgate insulator interface; 13) actually, we have confirmed that ® FE of our a-IGZO TFTs are close to or a little bit smaller than ® Hall . 1), 13) In this work, we investigated the effects of an O 2 -and ozone-(O 3 -) annealing combined process on characteristics of a-IGZO TFTs, and observed a high saturation mobility (® sat ) of ³30 cm 2 / Vs.…”
Section: Introductionsupporting
confidence: 53%
“…Based on the device physics, ® FE should be smaller than drift mobility (³® Hall ) because ® FE include the deterioration effects by electron traps in the band gap and carrier scattering at the channelgate insulator interface; 13) actually, we have confirmed that ® FE of our a-IGZO TFTs are close to or a little bit smaller than ® Hall . 1), 13) In this work, we investigated the effects of an O 2 -and ozone-(O 3 -) annealing combined process on characteristics of a-IGZO TFTs, and observed a high saturation mobility (® sat ) of ³30 cm 2 / Vs. However, these TFTs showed large charging/discharging currents in the gate-to-source current (I GS ).…”
Section: Introductionsupporting
confidence: 53%
“…As seen in Figure 2(b), the S value for a-IGZO TFTs may be as low as 100 mV/decade. The subgap DOS has been examined by several methods, including device simulation [65] and the capacitance-voltage (C-V) method [66], as shown in Figure 7. Th e subgap states near the CBM in a-IGZO is more than one order of magnitude lower than that in a-Si:H, and a low subgap DOS is the reason why AOS TFTs exhibit small S values and operate at low voltages.…”
Section: Si 3pmentioning
confidence: 99%
“…Especially, it is well known that oxygen pressure during oxide film deposition influences the formation of subgap density of states which play an important role in the TFT performance. 7 However, there is still much unknown physics of the density of states in oxide-based TFTs such as its effect on the device characteristics and bias stability, the defect physics, and so on. We have reported that a ZnO deposited under a low oxygen partial pressure included lots of donor-like traps near the conduction energy and these traps deteriorated the subthreshold characteristics of ZnO TFTs.…”
mentioning
confidence: 99%